Gaston Bachelard’s problems with psychoanalysis. Between Freud and Jung - Morawska, Kamila (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
The main field of reflection in the following article is devoted to the problems related to the reception of psychoanalysis in the thought of Gaston Bachelard. The author argues that Bachelard is more willing to refer to the depth psychology of C.G. Jung rather than classical Freudian psychoanalysis. In addition, if he takes the concept of an archetype from Jung, he does not understand the Freudian reflections. Bachelardian psychoanalysis is rationalized, draws from the wealth of the unconscious what it needs, and then quickly withdraws. Bachelard places his psychoanalysis on a less profound level than classical psychoanalysis does because he is not interested in descending to the organic level, but in working in a more superficial region where consciousness and unconsciousness mix, where culture leaves a mark on nature.